Omeprazole and Ranitidine in the Prevention of Relapse in Patients with Duodenal Ulcer Disease. (1st December 1999) - Lauritsen, K; Rutgersson, K; Bolling, E; Brunner, G; Eriksson, S; Galmiche, JP; Walan, A; Archambault, AP; Gudjónsson, H; Bailey, RJ; Bianchi Porro, G; Frison, L; et al.
Abstract : BACKGROUND: Although the eradication of Helicobacter pylori is of primary importance when initiating treatment, it is also important to have a strategy for patients who are H pylori -negative, fail to demonstrate eradication or have a tendency to become re-infected or relapse. PATIENTS AND METHODS: In a double-blind, parallel-group clinical trial of 928 patients (from 70 centres in 16 countries) with duodenal ulcers who after a short term study had relief of symptoms and healed ulcers proved endoscopically, 308 were randomly assigned to receive omeprazole 10 mg in the morning, 308 to receive omeprazole 20 mg in the morning and 312 to receive ranitidine 150 mg at bedtime for up to 12 months. Symptoms were assessed every three months and endoscopy repeated at three, six and 12 months, or more often if indicated by recurrence of symptoms. The safety screening included basal serum gastrin concentrations and gastric mucosal histopathology. RESULTS: The remission rates up to 12 months were 87% for the omeprazole 20 mg group, 71% for the omeprazole 10 mg group and 63% for the ranitidine group. Omeprazole 20 mg differed significantly from both omeprazole 10 mg (P=0.0001, 95% CI 9 to 23) and ranitidine (P=0.0001, 95% CI 17 to 31). There was no statistically significant difference between omeprazole 10 mg and ranitidine over the 12-month period, but the 95% confidence interval allowed differences between 0% and 16% in favour of omeprazole at 12 months. A Cox regression analysis revealed that longer treatment courses to heal, smoking, a long ulcer history and young age negatively contributed to the odds of staying in remission. The treatments were well tolerated. There was a slight increase in basal serum gastrin concentrations, reflecting the different degrees of acid inhibition induced by the three treatments. No dysplastic or neoplastic lesions were found in any biopsies. CONCLUSIONS: More duodenal ulcer patients are maintained in remission with omeprazole 20 mg daily than with omeprazole 10 mg daily or with ranitidine 150 mg at bedtime.